Do Th17 Lymphocytes and IL-17 Contribute to Parkinson's Disease? A Systematic Review of Available Evidence - Storelli, Elisa; Cassina, Niccolò; Rasini, Emanuela; Marino, Franca; Cosentino, Marco (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by progressive loss of dopaminergic neurons, appearance of Lewy bodies and presence of neuroinflammation. No treatments currently exist to prevent PD or delay its progression, and dopaminergic substitution treatments just relieve the consequences of dopaminergic neuron loss. Increasing evidence points to peripheral T lymphocytes as key players in PD, and recently there has been growing interest into the specific role of T helper (Th) 17 lymphocytes. Th17 are a proinflammatory CD4+ T cell lineage named after interleukin (IL)-17, the main cytokine produced by these cells. Th17 are involved in immune-related disease such as psoriasis, rheumatoid arthritis and inflammatory bowel disease, and drugs targeting Th17/IL-17 are currently approved for clinical use in such disease. In the present paper, we first summarized current knowledge about contribution of the peripheral immune system in PD, as well as about the physiopharmacology of Th17 and IL-17 together with its therapeutic relevance. Thereafter, we systematically retrieved and evaluated published evidence about Th17 and IL-17 in PD, to help assessing Th17/IL-17-targeting drugs as potentially novel antiparkinson agents. Critical appraisal of the evidence did not allow to reach definite conclusions: both animal as well as clinical studies are limited, just a few provide mechanistic evidence and none of them investigates the eventual relationship between Th17/IL-17 and clinically relevant endpoints such as disease progression, disability scores, intensity of dopaminergic substitution treatment. Careful assessment of Th17 in PD is anyway a priority, as Th17/IL-17-targeting therapeutics might represent a straightforward opportunity for the unmet needs of PD patients.